(untitled) (Journal of Universal Excellence, 2026)
Research Questions (RQ): What ethical dilemmas arise concerning the use of smartphones for private matters during working hours and what is the line between the acceptable use and the one that already has a negative impact on productivity? Purpose: Ethical dilemmas concerning the use of smartphones for personal matters during working hours have become very common and so far, they have not been researched enough. Therefore, the goal is to define the acceptable ethical rules based on the research. Methods: Firstly, we examined the existing scientific literature in the studied field with the help of which the basic concepts were explained. To substantiate the theoretical part of the thesis we employed two methods; the method of description and the method of compilation. Secondly, we used a quantitative approach, namely we conducted a survey and used (non)parametric tests. Results: The research has found that both managerial and non-managerial personnel completely agree that the ban on the use of smartphones during working hours for personal purposes is an expression of distrust, control and an invasion of privacy. Since the right to privacy is one of the most important human rights, the decision to limit the use of a smartphone during working hours for personal purposes should be carefully considered. Should the decision be made that it is necessary to establish or upgrade the code of ethics concerning the use of smartphone for private purposes during working hours the human rights aspects must be taken into consideration. Organization: The research examines ethical dilemmas in the field of smartphone use among employees for personal use during working hours in various organizations. The results of the research can be adopted by organizations as a starting point for addressing ethical dilemmas in the aforementioned area. Society: The research in the field of the ethical conduct of the use of smartphones among employees for private purposes during working hours can help the wider social environment in adequately addressing the above-mentioned challenges. Originality: The findings of the research can serve as an insight and help organizations in compiling or upgrading ethical rules/codes in the indicated field. Limitations/Future Research: The investigation of ethical dilemmas was done primarily due to concerns about potential productivity disruptions because of the use of smartphones. In the research, we limited ourselves only to medium-sized and large organizations in Slovenia that have already introduced the ISO standard, but it would be prudent to expand the research. Possible limitations of the research are also indicated in the concern that the respondents’ answers may be biased, and that they gave answers which are socially acceptable and/or desirable but not their honest opinion.